Three new small-flowered cyrtochilum species (orchidaceae: oncidiinae) from Colombia and Peru, and one new combination - Dalström, Stig (Universidad de Costa Rica, 2013)
Three new small-flowered Cyrtochilum species from Colombia and Peru are here described, illustrated and compared with similar species, and with one new taxonomic combination. The first species differs from all other Cyrtochilum species by the curved horn-like structures on the lip callus. The second species differs from its most similar relative by a larger flower with a different column structure. The third species is distinguished by the three horn-like knobs at the apex of the column.